2018
DOI: 10.1242/jeb.170902
|View full text |Cite
|
Sign up to set email alerts
|

Limits to sustained energy intake XXVII: trade-offs between first and second litters in lactating mice support the ecological context hypothesis

Abstract: Increased reproductive effort may lead to trade-offs with future performance and impact offspring, thereby influencing optimal current effort level. We experimentally enlarged or reduced litter size in mice during their first lactation, and then followed them through a successive unmanipulated lactation. Measurements of food intake, body mass, milk energy output (MEO), litter size and litter mass were taken. Offspring from the first lactation were also bred to investigate their reproductive success. In their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…Furthermore, an interaction of heat dissipation and peripheral limitation was also supported by several studies, suggesting that the limitation is dominated by different factors under different ambient temperature conditions (Speakman and Król, 2011;Zhao et al, 2016;Wen et al, 2017). An alternative 'trade-off' idea suggests that mammals may not maximise their lactation performance under all conditions, particularly if maximizing performance during the present reproduction would have a detrimental effect on their future reproductive performance or survival (Speakman and Król, 2005b;Piersma, 2011;Vaanholt et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, an interaction of heat dissipation and peripheral limitation was also supported by several studies, suggesting that the limitation is dominated by different factors under different ambient temperature conditions (Speakman and Król, 2011;Zhao et al, 2016;Wen et al, 2017). An alternative 'trade-off' idea suggests that mammals may not maximise their lactation performance under all conditions, particularly if maximizing performance during the present reproduction would have a detrimental effect on their future reproductive performance or survival (Speakman and Król, 2005b;Piersma, 2011;Vaanholt et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…The physiological basis of mechanisms imposing limits on E max during reproduction has been the matter of much debate (Drent and Daan, 1980;Hammond and Diamond, 1992;Koteja, 1996;Krol et al, 2007;Rogowitz, 1998;Wu et al, 2009). Several theories have been advanced to explain the apparent limits on E max (Hammond et al, 1996;Krol and Speakman, 2003a,b;Vaanholt et al, 2018;Wen et al, 2017). The two theories most supported by the current data are the 'peripheral limitations' theory Hammond and Kristan, 2000;Koteja, 1996;Rogowitz, 1998) and the 'heat dissipation limitation' (HDL) theory (Sadowska et al, 2016;Simons et al, 2011;Wu et al, 2009;Yang et al, 2013), or a combination thereof (Speakman and Król, 2011;Wen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…From an evolutionary perspective, a small litter is less worth investing in than a larger litter: Maestripieri and Alleva [ 43 ] demonstrated that CD-1 dams of large litters (eight pups) spent more than twice as much time displaying litter defense behaviors against intruder males than dams of small litters (four pups). The increase in pup death probability found in litters of 12 pups and above, on the other hand, may be a result of increased sibling competition for access to milk, as discussed above, and also may represent a ceiling in milk production capacity by the dams [ 22 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%